Discovery of two new polars evolved past the period bounce - Cunningham, Tim; Caiazzo, Ilaria; Sienkiewicz, Gracjan; Wheatley, Peter J.; Gänsicke, Boris T.; El-Badry, Kareem; Arcodia, Riccardo; Charbonneau, David; Connor, Liam; De, Kishalay; Hakala, Pasi; Kenyon, Scott J.; et al. (OXFORD UNIV PRESS, 2026)
We report the discovery of two new magnetic cataclysmic variables with brown dwarf companions and long orbital periods (Porb = 95 +/- 1 and 104 +/- 2 min). This discovery increases the sample of candidate magnetic period bouncers with confirmed sub-stellar donors from four to six. We also find their X-ray luminosity from archival XMM-Newton observations to be in the range L-X approximate to 1028-1029 ergs-1 in the 0.25-10 keV band. This low luminosity is comparable with the other candidates, and at least an order of magnitude lower than the X-ray luminosities typically measured in cataclysmic variables. The X-ray fluxes imply mass transfer rates that are much lower than predicted by evolutionary models, even if some of the discrepancy is due to the accretion energy being emitted in other bands, such as via cyclotron emission at infrared wavelengths. Although it is possible that some or all of these systems formed directly as binaries containing a brown dwarf, it is likely that the donor used to be a low-mass star and that the systems followed the evolutionary track for cataclysmic variables, evolving past the period bounce. The donor in long period systems is expected to be a low-mass, cold brown dwarf. This hypothesis is supported by near-infrared photometric observations that constrain the donors in the two systems to be brown dwarfs cooler than approximate to 1100 K (spectral types T5 or later), most likely losing mass via Roche Lobe overflow or winds. The serendipitous discovery of two magnetic period bouncers in the small footprint of the XMM-Newton catalogue implies a large space density of these type of systems, possibly compatible with the prediction of 40-70 per cent of magnetic cataclysmic variables to be period bouncers.